Preen gland microbiota of songbirds differ across populations but not sexes. Issue 9 (22nd June 2021) - Grieves, Leanne A.; Gloor, Gregory B.; Kelly, Tosha R.; Bernards, Mark A.; MacDougall‐Shackleton, Elizabeth A.
Abstract: Metabolites produced by symbiotic microbes can affect the odour of their hosts, providing olfactory cues of identity, sex or other salient features. In birds, preen oil is a major source of body odour that differs between populations and sexes. We hypothesized that population and sex differences in preen oil chemistry reflect underlying differences in preen gland microbiota, predicting that these microbes also differ among populations and between the sexes. We further predicted that pairwise similarity in the community composition of preen gland microbiota would covary with that of preen oil chemical composition, consistent with the fermentation hypothesis for chemical recognition. We analysed preen oil chemistry and preen gland bacterial communities of song sparrows Melospiza melodia . Birds were sampled at sites for which population and sex differences in preen oil have been reported, and at a third site that has been less studied. Consistent with prior work in this system, we found population and sex differences in preen oil chemistry. By contrast, we found population differences but not sex differences in the community composition of preen gland microbes. Overall similarity in the community composition of preen gland microbiota did not significantly covary with that of preen oil chemistry. However, we identified a subset of six microbial genera that maximally correlated with preen oil composition. Although both preen gland microbiota and preen oil composition differ across populations, we did not observe an overall association between them that would implicate symbiotic microbes in mediating variation in olfactory cues associated with preen oil. Instead, certain subsets of microbes may be involved in mediating olfactory cues in birds, but experiments are required to test this. Abstract : The authors found population differences in the preen gland microbiota of song sparrows, a widespread North American passerine. Both preen gland microbes and preen oil chemicals differed across populations, but there was no overall association between them. Instead, a subset of preen gland microbes may mediate variation in olfactory cues associated with preen oil.